Implementasi Histopreneurship dalam Mata Kuliah Historiografi pada Mahasiswa Prodi Sejarah IKIP Budi Utomo - Debi Setiawati; Fatmawati (Universitas Insan Budi Utomo, 2023)
The development of science in the millennium has influenced the changing challenges of higher education in society. For this reason, higher education must be able to answer these challenges by making various innovations in learning, one of which is through the KKNI-based higher education curriculum, which can integrate the education sector with the job training sector. The development of a histopreneurship-based historical learning model is one way to answer the challenges of today's history teachers. History teachers can have historical competences and entrepreneurial skills that can be implemented in society. This study uses the ADDIE model Research and development (R and D) development method which has five stages, namely: analysis, design, development, implementation and evaluation. The results of this study indicate that the Histoprenership Learning Model can improve students' critical thinking skills in capturing opportunities in the creative industry in society. Histoprenership learning model can increase the entrepreneurial spirit of students, resulting in a paradigm shift in thinking that history students do not have to be job seekers but can open new jobs.